MAS4SSP: A Multi-Agent Reference Architecture for the configuration and monitoring of Small Series Production lines - Roloff, Mario Lucio; Amaral, Cleber Jorge; Stivanello, Mauricio Edgar; Stemmer, Marcelo Ricardo (INDUSCON 2016 : 12th IEEE/IAS International Conference on Industry Applications : November 20-23, Curitiba, 2016)
The contribution of this paper is the presentation of a new Multi-Agent Reference Architecture for the configuration and monitoring the Small Series Production lines (MAS4SSP). The approach brings, specially, flexibility and a substantial decrease of machines setup time. It proposes an architecture based on a unified, synergic and high level of abstraction solution using as reference model JaCaMo framework, which follows the Multi-Agent Oriented Programming (MAOP). The integration with the production line is accomplished with the use of Web Service communication technology. Web Services are used in the Multi-Agent System (client side) and in the SCADA system (server side). A simple user interface was developed in Java to order batches of products, as alternative, legacy production systems (such as ERP, PPC, MRP and so on) can be integrated by the Web Service Application Programming Interface. This model was instantiated in a controlled experiment, a small series production line of Printed Circuit Boards (PCB). Results and conclusions are presented in the article.